The use of loose salt for fattening pigs on corn, tankage and alfalfa hay in the dry lot. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2012)
The Department of Animal Husbandry has recently received a number of requests for information on the need of salt for fattening pigs when the ration was corn and tankage with alfalfa hay or pasture. The answer to these inquiries has always been that pigs did not need salt when they received tankage or some similar protein supplement of animal origin; but if most of the protein supplement was of plant origin as soybean meal, cottonseed meal, alfalfa meal, or linseed meal, salt was advisable.
Keywords: Swine; Salt; Corn; Alfalfa